Breakdown of Self-Incompatibility in a Natural Population of Petunia axillaris Caused by Loss of Pollen Function - Tsukamoto, Tatsuya (American Society of Plant Biologists, 2003)
Although Petunia axillaris subsp. axillaris is described as a self-incompatible taxon, some of the natural populations we have identified in Uruguay are composed of both self-incompatible and self-compatible plants. Here, we studied the self-incompatibility (SI) behavior of 50 plants derived from such a mixed population, designated U83, and examined the cause of the breakdown of SI. Thirteen plants were found to be self-incompatible, and the other 37 were found to be self-compatible. A total of 14 S-haplotypes were represented in these 50 plants, including two that we had previously identified from another mixed population, designated U1. All the 37 self-compatible plants carried either an S(C1)- or an S(C2)-haplotype. S(C1)S(C1) and S(C2)S(C2) homozygotes were generated by self-pollination of two of the self-compatible plants, and they were reciprocally crossed with 40 self-incompatible S-homozygotes (S(1)S(1) through S(40)S(40)) generated from plants identified from three mixed populations, including U83. The S(C1)S(C1) homozygote was reciprocally compatible with all the genotypes examined. The S(C2)S(C2) homozygote accepted pollen from all but the S(17)S(17) homozygote (identified from the U1 population), but the S(17)S(17) homozygote accepted pollen from the S(C2)S(C2) homozygote. cDNAs encoding S(C2)- and S(17)-RNases were cloned and sequenced, and their nucleotide sequences were completely identical. Analysis of bud-selfed progeny of heterozygotes carrying S(C1) or S(C2) showed that the SI behavior of S(C1) and S(C2) was identical to that of S(C1) and S(C2) homozygotes, respectively. All these results taken together suggested that the S(C2)-haplotype was a mutant form of the S(17)-haplotype, with the defect lying in the pollen function. The possible nature of the mutation is discussed.